Review: Interconnecting translation studies and imagology. Luc van Doorslaer, Peter Flynn, Joep Leerssen (eds.). Amsterdam/Philadelphia: John Benjamins Publishing Company, 2016. Pp. vii, 333 - Fornalczyk-Lipska, Anna (Studia Anglica Posnaniensia, 2016)
Rewiew: Interconnecting translation studies and imagology. Luc van Doorslaer, Peter Flynn, Joep Leerssen (eds.). Amsterdam/Philadelphia: John Benjamins Publishing Company, 2016. Pp. vii, 333.